Analysis of Free Fall Motion Using the Double-Switch Laboratory Method with Iron Balls - Mikael Namas; Felisianus Efrem Jelahut; Mutiara Meldisari Mnahonim; Mikael Namas; Felisianus Efrem Jelahut (Universitas Negeri Malang, 2026)
The purpose of this research is to determine the magnitude of the acceleration of gravity on the free fall motion and in analyzing this research is to determine the magnitude of the acceleration of a free fall object which depends on the magnitude of the force that affects the object by varying the distance the object will be dropped. Data collection in this research uses an experimental method. The subject of this research is the magnitude of the acceleration of the free fall object, in the falling motion, variations in the height of the object's fall will be carried out, 75 cm and 90 cm with the mass of the object ignored, the data needed is the free fall object by analyzing the iron ball that will be dropped at different heights. To be able to find out the magnitude of the acceleration of an object in free fall motion, an analysis will be carried out using the formula in the theory, and the time required in this research is six months. Based on the analysis that has been used, the value of the acceleration of the object's motion for a large iron ball and for a small iron ball, the average value is (4.84 ms-2 ± 4.54) ms-2 and the magnitude of the object's velocity falling at a height of 75 cm for a large iron ball and for a small iron ball, the average value is (2.6544 ms-1 ± 2.8302) ms-1 and for a height of 90 cm, the average value of the velocity is (2.6544 ± 2.8302) ms-1.